School social workers' perceptions of electronic media on practice - Keeney, Adrianne Jane, author; Buchan, Victoria, advisor; Quijano, Louise, committee member; Hughes, Shannon, committee member; Marx, Nick, committee member (Colorado State University. Libraries, 2017)
Electronic media has provided new challenges and opportunities for school social workers. The use of electronic communication to interact with others is a normative and daily part of life for children, adolescents, and adults. Currently there are few, if any guidelines regarding electronic media behavior and standards for school social work practice. The purpose of this study was to explore the perceptions, beliefs, and experiences from the perspective of school social workers on how electronic communication has affected their practice. A phased research design with quantitative and qualitative components was utilized for this exploratory research. Data from (N=379) school social workers practicing in the United States were collected. A combination of descriptive, correlation, exploratory factor analysis, and analysis of variance were used to analyze differences and associations among school social worker responses based on current age of the practitioner, community of practice, and student population served. Age associations were found with the incorporation of electronic elements in service delivery as well as digital knowledge being perceived as a factor impacting the ability to effectively problem solve. School social workers' incorporation of electronic media into service delivery was found to vary depending on the student population served. Age, community of practice or population served were not found to be a contributing factor to ethical dilemmas encountered or the perceived need for electronic media policies to further inform practice. Guidelines related to mandated reporting in regards to electronic communication and social media boundary guidelines were the top two policies that respondents identified needing the most to further inform their practice. Results suggest that school social workers perceive their practice is affected due to electronic media and these perceptions may differ based upon age, community of practice and population served. It is hoped that the results of this research would be used to guide: (1) recommendations for professional practice policies and social work education; (2) future research that will further inform school social work practice and support school social workers providing services in a digital era.
Keywords: electronic media; school social work; social work practice; perceptions; electronic communication; social media